Spatial dependence in the cyclical sensitivity of labour supply: An analysis at the regional level in Ecuador - Ángel Maridue\~na-Larrea; Ángel Martín-Román (Economies, 2024)
The labour supply has historically been subject to influence from the economic cycle. On the other hand, there is a paucity of research in the Latin American region examining the impact of social factors on labour participation in diverse contexts. This study examines the spatial dependence of the cyclical sensitivity of labour supply in 23 provinces of Ecuador. A time series analysis was conducted to calculate the cyclical sensitivities of labour supply, and spatial econometric techniques were applied to assess spatial dependence using monthly data for the period 2021 to 2024. We found evidence of a positive and significant spatial dependence in the cyclical sensitivity of labour supply. Our findings suggest that labour decisions in one province are influenced by those in neighbouring provinces, thereby providing a framework for the design of public policies that take into account these interdependencies.
Keywords: C23; D03; E32; J21; R23; 330; added worker effect; discouraged worker effect; bandwagon worker effect; labour participation rate; spatial dependence; business cycle